Representasi Identitas Kain Tenun pada Desain Visual Sarung BHS - Irwan Widodo; Zulfikar Sa’ban (Tamilis Synex: Multidimensional Collaboration, 2024)
The cloth used for clothing is a marker of identity for various groups and individuals. One of the uses of cloth is the BHS Sarong, which is a woven sarong made from Indonesia whose quality is unquestionable. BHS sarongs are one of the proud products of the Indonesian people because they are famous for their quality, motifs and traditions of cultural preservation. This study aims to discuss and analyze the visual design of the completeness of the original BHS sarong stamp as the identity of woven fabrics. This research is a qualitative descriptive research with research stages consisting of conducting research, clarifying strategy, designing identity, creating touchpoints, and managing assets. The research approach used in this study is a qualitative approach, in which the data sources come from interviews, documentation, and material involvement through direct experience emphasizing sensory and direct manipulation. The results showed that the design of visual identity was carried out to reintroduce the BHS Sarong product, which is the best sarong product made from woven fabric. The visual identity stage consists of conducting research, clarifying strategy, designing identity, creating touchpoints and managing assets that produce logos, stamps and signatures for original BHS sarong products.